Leveraging agrigenomics" for crop improvement" - Gedil, Melaku A; Rabbi, Ismail Y. (2012)
Modern biotechnologies have dramatically reshaped the crop improvement research during the past decade. Biotechniques have become indispensable for efficient and effective development of new knowledge, processes, and products. IITA's biotechnology, strategized as three major themes― genomics, transgenics, and diagnostics, is directed toward the genetic improvement of staple food crops of Africa, such as cooking-banana, plantain, cassava, yam, and cowpea. This section provides some insights and progress in this program.